BIMBINGAN TEKNIS PENANGANAN PASCA PANEN BULU BABI DI KOPERASI PRIMA NUSANTARA - Asri, Yuliana; Hizbulloh, Lalu; Affandi, Rangga Idris; Lumbessy, Salnida Yuniarti; Diamahesa, Wastu Ayu; Mulyani, Laily Fitriani; Alim, Sahrul; Lestari, Dewi Putri; Scabra, Andre Rachmat; Marzuki, Muhammad (Jurnal Pepadu, 2025)
Sea urchins are a highly nutritious and economically valuable fishery product. In West Nusa Tenggara (NTB), particularly in Lombok, the public is still largely unaware of the benefits and market value of sea urchins in international markets such as Japan and Korea. Sea urchin gonads are consumed by Koreans and Japanese, and their high nutritional content is believed to improve health performance. However, there are obstacles in the sea urchin market development is the lack of proper standard operating procedures in post-harvest handling. Appropriate and standardized post-harvest techniques are not yet widely known or disseminated among sellers and sea urchin business actors. Prima Nusantara Cooperative is one of the cooperatives that supplies fishery products, including sea urchins, to exporting companies. Based on this, the current community service activity was conducted at Prima Nusantara Cooperative in East Lombok, targeting the cooperative staff. The aim is to provide both theoretical socialization and hands-on training to enhance the staff’s knowledge and skills in post-harvest handling of sea urchins. Through this technical guidance, it is expected that the quality of sea urchin products sold to exporters will improve and be more competitive in the Japanese and Korean markets. The method used during the technical training included presentation of materials on proper sea urchin handling procedures, followed by field practice involving sea urchin sampling, hands-on demonstrations, and direct mentoring through each stage of the process. The post-harvest handling stages included harvesting (collection), cleaning, shell breaking, rinsing, weighing, packaging, and storage at low temperatures.